Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/cancers15030777
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and Modulating Diet and Gut Microbes to Enhance Response and Reduce Toxicity to Cancer Treatment

Abstract: The gut microbiome comprises a diverse array of microbial species that have been shown to dynamically modulate host immunity both locally and systemically, as well as contribute to tumorigenesis. In this review, we discuss the scientific evidence on the role that gut microbes and diet play in response and toxicity to cancer treatment. We highlight studies across multiple cancer cohorts that have shown an association between particular gut microbiome signatures and an improved response to immune checkpoint bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 150 publications
0
1
0
Order By: Relevance
“…Furthermore, one of our patients who demonstrated diarrhea control after FMT was presumed to have CRC originating from the stomach-which highlighted the complexity of cancer pathogenesis and the potential of FMT in modulating gastrointestinal health. Overall, these ndings support the e cacy and safety of FMT in mitigating AEs of cancer treatments, warranting further research into relevant underlying mechanisms and broader applications [30]. Both experimental and clinical investigations have revealed substantial correlations among microbial taxa, intestinal dysbiosis, treatment-induced toxicity, and anticancer therapy effectiveness [31][32][33][34].…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, one of our patients who demonstrated diarrhea control after FMT was presumed to have CRC originating from the stomach-which highlighted the complexity of cancer pathogenesis and the potential of FMT in modulating gastrointestinal health. Overall, these ndings support the e cacy and safety of FMT in mitigating AEs of cancer treatments, warranting further research into relevant underlying mechanisms and broader applications [30]. Both experimental and clinical investigations have revealed substantial correlations among microbial taxa, intestinal dysbiosis, treatment-induced toxicity, and anticancer therapy effectiveness [31][32][33][34].…”
Section: Discussionmentioning
confidence: 78%
“…Consequently, it was suggested that diet should be considered as a potential prevention or treatment for cancer treatment adverse effects [59]. Indeed, a recent review discussed the importance of targeting dietary intake around the production of key bacterial taxa, such as Bacteriodes and Firmicutes, in order to modulate adverse effects [71]. For example, it is understood that high fibre diets lead to an increased production of SCFA's [72,73], potentially reducing the prevalence and severity of adverse effects.…”
Section: Potential Interventions Targeting Gut Microbiome To Modulate...mentioning
confidence: 99%